2016
DOI: 10.1021/acssuschemeng.6b01623
|View full text |Cite
|
Sign up to set email alerts
|

Greener and Sustainable Trends in Synthesis of Organics and Nanomaterials

Abstract: Trends in greener and sustainable process development during the past 25 years are abridged involving the use of alternate energy inputs (mechanochemistry, ultrasound- or microwave irradiation), photochemistry, and greener reaction media as applied to synthesis of organics and nanomaterials. In the organic synthesis arena, examples comprise assembly of heterocyclic compounds, coupling and a variety of other name reactions catalyzed by basic water or recyclable magnetic nanocatalysts. Generation of nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(135 citation statements)
references
References 129 publications
1
127
0
Order By: Relevance
“…The Sulfonated graphitic carbon nitride (Sg-CN) has been designed and synthesized via sequential calcination333435 and sulfonation of urea (Fig. 1).…”
Section: Synthesis and Characterization Of Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sulfonated graphitic carbon nitride (Sg-CN) has been designed and synthesized via sequential calcination333435 and sulfonation of urea (Fig. 1).…”
Section: Synthesis and Characterization Of Catalystmentioning
confidence: 99%
“…Engaged in the development of sustainable methods and converting waste products into valuable chemicals3031323334, herein, we report the use of sulfonated graphitic carbon nitride (Sg-CN) as a benign and cost effective organo-sulfonated heterogeneous acid catalyst for the synthesis of biodiesel.…”
mentioning
confidence: 99%
“…the environmentally benign solvent medium (water and ionic liquid-based green solvents) for the synthesis of NPs; gum acts as reducing agent due to the presence of many functional groups in the gum structure (-OH, -COO-, -CO, and CH 3 CO-) and gums are non-toxic and biodegradable materials for the stabilization of NPs. However, even today, many studies have reported the use of toxic solvents such as organic solvents, and toxic, highly reactive and environmentally and biologically risky reducing agents such as hydrazine, sodium borohydride and dimethyl formide, and capping agents such as EDTA, triethanolamine and tetraethylammonium bromide, which are known to bio-accumulate in the environment and are persistent pollutants, which may have ecological or human health risks, used for the synthesis of NPs [8][9][10]17]. …”
Section: Tree Gums As a Natural Renewable Source For The Green Synthementioning
confidence: 99%
“…Nanoscale filtration techniques, the adsorption of pollutants on nanoparticles and the breakdown of contaminants by nanoparticle catalysts are the major applications of nanotechnology in the clean-up of contaminated water [8][9][10]. The advantages of electrospun nanofibre membranes are that they can offer both adsorption and filtration characteristics.…”
Section: Applications Of Electrospun Nanofibres For Environmental Biomentioning
confidence: 99%
See 1 more Smart Citation